Pengaruh Fraksi Tak Larut N-Heksana dari Ekstrak Etanol Daun Seligi (Phyllanthus buxifolius Muell.Arg) terhadap Daya Antiinflamasi pada Mencit yang terinduksi Karagenin - Siwi Putri Handayani; Siwi Hastuti (Indonesian Journal on Medical Science, 2023)
Seligi (Phyllanthus buxifolius Muell. Arg) has been used empirically as a painkiller and anti-inflammatory. The purpose of this study was to determine the anti-inflammatory power of the n-hexane insoluble fraction from the ethanol extract of Seligi leaves in carrageenin-induced mice. The isolation method was carried out by maceration and fractionation. Mice were given the test preparation orally and then induced using a 0.1% carrageenin solution intraplantarly. The length of the edema was observed by measuring the diameter of the soles of the mice's feet. Udem length to determine the percentage of anti-inflammatory power (% DAI). One way ANOVA test as statistical analysis and post hoc test. The percentage of anti-inflammatory power in a row the insoluble fraction of the ethanol extract of Seligi leaves doses of 200, 400 and 800 mg/kg BW were (49.24 ± 0.65)%, (56.01 ± 1.58)% and (65.03 ±1.16)%, while diclofenac sodium 6.5 mg/kgBW has a %DAI of (66.16±1.96)%. There is a significant difference shown from the results of the one way ANOVA test. In the post hoc test, there were significant differences between the treatments, except for the highest dose fraction, which was 800 mg/kgBW with diclofenac sodium at a dose of 6.5 mg/kgBW. The content of flavonoids in the fraction can reduce inflammation in mice. Seligi leaf fraction preparations have the potential for local wisdom as an anti-inflammatory.